Microbiological spectrum of pathogens in cardiac surgery patients in the intensive care unit - К.П. Чиж; Т.А. Малишева; А.П. Мазур (Медицина неотложных состояний)
Background. Intensive care unit (ICU) patients are at high risk of hospital-acquired infections, which is a significant problem in modern medicine. Every year, 140,000 deaths from hospital-acquired infections are reported. For example, studies in the United States show that 30 % of infections occur in the ICUs. The presence of hospital-acquired flora in patients prolongs their stay in the ICU, increases the duration of antibiotic therapy, and treatment costs. The occurrence of such an infection is the result of a complex interaction of pathogenic (virulence, antibiotic resistance), patients’ (comorbidities, acute illnesses, emergency surgery), and treatment factors (invasive devices), and the work of the health care system (staffing, preventive measures). Mortality among individuals with a positive bacteriological blood test reaches 25 % among all patients in the intensive care unit, which emphasizes the importance of timely diagnosis and control of such infection. The analysis of the microbiological spectrum of pathogens in cardiac surgery patients is a complex process, but it is quite possible and necessary to improve the effectiveness of treatment of cardiac surgery patients. Objective: to analyze the microbiological spectrum of pathogens in cardiac surgery patients in the ICU. Materials and methods. The study included retrospective clinical data of 323 patients who were treated in the preoperative or postoperative period at the intensive care unit of the State Institution “Amosov National Institute of Cardiovascular Surgery of the National Academy of Medical Sciences of Ukraine” from January 1, 2021, to December 31, 2023. The entire cohort had a positive bacteriological blood test. The microbiological analysis was performed using a Vitek 2 Compact analyzer with a BACT/ALERT 3D60 colometric system for detecting bacterial growth (No. VK2C8748). The microbiological spectrum of pathogens in cardiac surgery patients in the intensive care unit was analyzed. Results. In 2021, 81 patients had a positive microbiological blood test. The incidence of pathogens was as follows: gram-positive infection — 69 (85.1 %), gram-negative infection — 11 (14.6 %), fungi of the genus Candida — 1 (0.3 %) case, respectively. In 2022, 95 patients had a positive microbiological blood test. The frequency of pathogens was as follows: gram-positive infection — 75 (78.9 %) cases, gram-negative infection — 20 (21.1 %). In 2023, 147 patients had a positive microbiological blood test. The incidence of pathogens was as follows: gram-positive infection — 97 (66.0 %) cases, gram-negative infection — 46 (31.3 %) cases, Candida fungi — 4 (2.7 %) cases, respectively. Conclusions. An increase was found in the frequency of Klebsiella spp. microorga-nisms from 60 to 84 % of cases from the total spectrum of gram-negative pathogens in the ICU in 2023. There was a decrease in the frequency of Enterobacter spp. from 22 % of cases in 2021 to 13 % in 2023. The proportion of identified Acinetobacter spp. pathogens decreased from 11 % of cases in 2021 to 3 % in 2023.